Analysis of Perception towards Ecology in Ecotourism Development in Sleman Regency - Evareny Yustina; Ricky Avenzora; Tutut Sunarminto (Media Konservasi, 2017)
The study on the ecology perception is important to support ecotourism development in Sleman Regency. The objectives of this study are to create an effective strategy among stakeholders that ensures the sustainability of ecology in ecotourism development in Sleman. This study was conducted in Sleman Regency involving groups of respondent who are stakeholders of ecotourism in Sleman Regency. Data was collected using a closed-ended questionnaire with a scale of 1-7. The result shows that the stakeholder’s perception in Sleman Regency is varied and an effective strategy is necessary for the development of a sustainable ecotourism. Keywords: ecology, ecotourism, perception, Sleman, sustainable